Examining the Factorial Structure of the Maternal Separation Anxiety Scale in a Portuguese Sample - Guedes, Maryse; Monteiro, Lígia; Santos, António J.; Torres, Nuno; Veríssimo, Manuela (Frontiers in Psychology, 2021)
The increase in women’s labor market participation emphasizes the importance of understanding maternal separation anxiety, that is, the unpleasant maternal emotional state, due to the actual or anticipated short-term separation from the child. Drawing on the insights of the attachment and psychoanalytic perspectives, the Maternal Separation Anxiety Scale (MSAS) was developed to overcome existing measurement gaps. However, there are still inconsistencies on the replicability of its original three-factors structure in other cultural contexts, using large and diverse samples, in terms of child’s age. This study aimed to examine the factorial structure of the MSAS in a sample of 597 Portuguese mothers of children aged 5 to 84 months, who completed the questionnaire. The exploratory factor analysis conducted in subsample 1 revealed a four-factors structure: Maternal Negative Feelings, Beliefs about Exclusive Maternal Care, Need of Proximity and Perceptions of Separation Benefits for Children. Confirmatory factor analyses conducted in subsample 2 revealed that the original three-factors structure revealed a poor fit, whereas the four-factors solution (obtained in the exploratory factor analysis) revealed an acceptable fit. As in previous studies, our findings report deviations from the original three-factors structure of the MSAS. Three of the newly identified factors seem to reflect specific sub-dimensions that originally guided item development in the MSAS, namely maternal negative feelings, maternal attitudes about the value of exclusive maternal care, and the need of proximity with the child. The last factor appears to represent a refinement of original items pertaining to perceptions about separation effects for children.